Development and in vitro characterization of a mucoadhesive gel with Moringa oleifera extract for periodontal drug delivery - Minnu Joe Ida; Bhavya Shetty; Safiya Fatima Khan; Umesh Yadalam; Manjusha Nambiar (Wolters Kluwer Medknow Publications, 2023)
Background: Extensive in vitro and in vivo research has been conducted in the previous decades to analyze the effectiveness of medicinal plants in the treatment of periodontal diseases. Moringa oleifera is a highly potent medicinal plant that has anti-inflammatory and immuno-modulatory properties. In our study, we aim to design, formulate, and evaluate the antibacterial efficacy of M. oleifera extract for local drug delivery (LDD) as periodontal treatment. Materials and Methods: This study was an in vitro experimental model. M. oleifera extract was prepared using a maceration process with powdered dried leaves of M. oleifera and 70% ethanol. The minimum inhibitory concentration (MIC) of Moringa extract against Porphyromonas gingivalis was assessed using the broth dilution method. The gel was prepared with the obtained MIC of Moringa extract and a combination of polymers- Polyethylene glycol 6000, Carbopol 940, and Chitosan. Further, the formulated gel was subjected to in vitro characterization by thermodynamic stability tests, pH determination, and syringeability test. Viscosity was determined using Brookfield DV-II + Viscometer. Mucoadhesive strength was determined using a fabricated mucoadhesive strength test apparatus. Results: M. oleifera leaves extract possesses a bactericidal effect against P. gingivalis even at a low amounts of 25 μg/ml and so is a potent botanical extract for the formulation of LDD agents for periodontal diseases. The formulation shows adequate stability, good mucoadhesiveness, and controlled drug release, on incorporating the herbal extract into the blank gel. Conclusion: The M. oleifera leaves extract possesses a bactericidal effect against P. gingivalis which has been suggested to be the keystone pathogen in the etiopathogenesis of periodontitis. Hence, M. oleifera leaves extract can be used to treat periodontal diseases as a LDD agent.